PENERAPAN PENDIDIKAN MULTIKULTURAL UNTUK MI/ SD DALAM PERSPEKTIF ISLAM - Daluti Delimanugari (Tarbiya Islamica, 2022)
Multicultural Education is education that should be mandatory in basic education in both SD and MI. Because multicultural education is education about cultural diversity in response to demographic and cultural changes in a particular community or even the world as a whole or globally. Islam has also taught a lot about how to respect multiculturalism itself, both in the Al-Quran and in the Medina charter. This study uses a literature study research method. Derived from various references to find research results. The results of the discussion of this study are that the attitudes that must be developed in multicultural education for MI/SD students are as follows. The first is egalitarianism or al-musawat which views humans as equals. Justice or al-adalat, mutual tolerance or tasamuh, ties of friendship, the principle of peace or al ta'ayus al silmi, and finally wise, constructive and transformative dialogue or mujadalat bi al-hasan. If all these attitudes grow in the souls of MI/SD children, a harmonious, peaceful life will be created in accordance with Islam which is rohmatan lil alamin.